Barriers to the Implementation of the Articles of Continuing Acts in the Law of Criminal Acts of Corruption in Indonesia - Kaplele, Farida; Suseno, Sigid; Sulistiani, Lies; Rusmiati, Elis (International Journal of Criminology and Sociology, 2021)
The problem that will be discussed in this paper is the problem of obstacles to eradicating criminal acts of corruption regulated in the Corruption Crime Act in Indonesia, which in its implementation is often associated with the existence of norms in Article 64 Paragraph (1) of the Indonesian Criminal Code which regulates criminal acts. (voorgezette handling) corruption in Indonesia. To overcome this problem, a search for documents and literature studies was carried out, a study of laws and regulations, including decisions on corruption cases that had existed, then carried out a descriptive analysis to solve the problem. The study results show that the obstacles in the application of Article 64 of the Criminal Code are related to continuing acts of corruption in Indonesia. First, the difficulty of separating a criminal act as a single offense if it is carried out by state officials who handle the same problem and project every time. Day; Second, it is often interpreted that the will's decision is an act of corruption itself; Third, the determination of material actions (feit materieele); and Fourth, continuous action is not only seen as a rule relating to the issue of the imposition of crime and the weighting of criminal acts.